Assessing The Coverage, Adequacy and Accessibility of Selected Community Facilities For Malaysian Elderly Based on GIS Approach - Lim, Che Kiong (2005)
The numbers of elderly in the population nowadays have grown tremendously and benefited from the modern development of better community services especially in countries where there are great advancement and progression in health technology. This emphasis on improvement of community facilities has undoubtedly provided a better quality of life to many of the older generation and undeniably help in increasing their life span, hence the increase in population. Contrary to this, many from the older generations are still faced with difficulties in getting access to the provided services because of problems in efficiency of facilities provision. In conjunction to this, many initiatives have been taken by the associated government agencies dedicated to meet the needs of the elderly. The dedications are in terms of easier access to the available facilities and without having to pay an astronomical fee. But the planning for the elderly is a complex issue because their needs are as varied as the population composition itself. On the other hand, conventional method of data collection (hardcopy based) has been found to be inefficient and ineffective in terms of producing qualitative results within a short time span. The two primary objectives guide this research whlch is analysis of the coverage, adequacy and the accessibility of selected community fachties for the elderly through the GIs technology, and second is to create an automated data collection technique by using the PDA. Methods in use involve PDA program customization, selection and surveymg of targeted sites in terms of accessibility to the selected community facilities. All collected PDA data are pooled and incorporated into the GIs database. This is followed by creation of elderly database for spatial analysis and accessibhty analysis. From the experimental results, the used of automated data collection PDA system is much more cost-effective and time saving. Besides, with the aid of GIs technology, the distributions of demographic of elderly in different characteristic are clearly determined based on several definitions. The study successfully demonstrated the application of GIs with the several methods in the facilities accessibility assessment of the targeted group, and it has been found that the community fachties are barely adequate in study area. As an addition, an automated data collection technique and complimentary spatial analysis procedures can help to encourage better decision modeling in the development of a better health care for the elderly. With this automated GIs system, it is hope that better planning and decision modeling can be done. Thus is to ensure that problems of specific needs of the target group, in relation of accessibility to social and health facilities, wil be reduced and finally overcome albeit slowly.